Pengaruh Pengawasan Terhadap Disiplin Kerja Karyawan Pada Hotel Sintesa Peninsula Manado - Jisiani A. B. Sigar; Sofia A. P. Sambul; Sandra Asaloei (Universitas Sam Ratulangi, 2018)
Supervision is one of the several functions of management within the organization, which has the meaning of a process of supervising and evaluating an activity. When doing a job, there’s a rules that have been established and is mandatory to be obeyed by all people who work in that place. The activities in organization without an supervision caused work discipline decreased and will affect to other activities which hindred the process of achieving the goals. Every company including Sintesa Peninsula Hotel Manado, definitely want to provide satisfactory service for the customer, for that hotel should give the maximal and valuable service to the costumers. In order to give the maximal and valuable service, the employees have to provided to give value to customers, so the employees should be diligent in working and doing their jobs, especially hotel working system closely related to timing. Bad service caused dissatisfaction. This research was conducted on the employees of Sintesa Peninsula Hotel Manado by using the quantitative method to find out whether supervision can affect employees work discipline in Sintesa Peninsula Hotel Manado. The results of this study indicate that supervision affects employee work discipline at Hotel Sintesa Peninsula Manado where supervision has been applied and have positive impact to the employees.Keywords : Supervision, Work Discipline.